Real world survival data of a rare malignancy: Anal cancer results in HIV negative patients from Turkey - Esin, Ece; Yıldız, Ferah; Laçin, Şahin; Karakaş, Yusuf; Gültekin, Melis; Yalçın, Şuayib (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: An organ preservation approach using chemoradiotherapy has been established for anal cancer. This retrospective cohort study aimed to define the clinico-demographic characteristics and outcomes of cases of human immunodeficiency virus (HIV)-negative anal carcinoma during a period of 20 years in a single comprehensive cancer institute. Materials and Methods: This was a single-center retrospective cohort study of patients who were treated between January 1995 and January 2015. The primary outcome measures that were investigated included overall survival (OS), progression-free survival (PFS), colostomy rates, and colostomy-free survival (CFS). Results: A total of 28 patients who were principally treated with standard 5-fluorouracil + mitomycin combination chemoradiotherapy were eligible for analysis. The 3- and 5-year PFS rates were 92.4% and 63%, respectively. The lower T stage was found to be associated with a prolonged PFS (p=0.001). The 3- and 5-year CFS rates were 84.3% and 74.9%, respectively. A longer CFS was observed with lower T stages (p=0.05). At the last follow-up, 75% of the patients with anal cancer were alive, and 71.4% of the patients were disease free. The median OS was not reached Cite this article as: Esin E, Yıldız F, Laçin Ş, et al. Real world survival data of a rare malignancy: Anal cancer results in HIV negative patients from Turkey. Turk J Gastroenterol 2018; 29: 411-8.